Pelatihan pembuatan Briket Arang Untuk Meningkatkan Kemandirian Ekonomi Bagi Ibu PKK dan UMKM Desa Karangdayu - saida, ita aristia saida (Nawasena Bhakti, 2025)
Karangdayu Village has abundant potential in organic waste such as coconut shells, sawdust, and rice husks, but these resources have not been optimally utilized by the local community. The main issues faced include the low level of waste processing skills and limited access to relevant knowledge and training, particularly among PKK women's groups and micro, small, and medium enterprises (MSMEs). The objective of this community service activity is to improve the community’s skills in processing waste into economically valuable products, specifically through charcoal briquette production training. The service methods include stages such as socialization, hands-on training, evaluation during and after the training, and sustainability strategies through the formation of small business groups. The results show that participants developed a good understanding of briquette production techniques and were able to practice the process independently. Moreover, the formation of business groups managed by PKK and MSMEs marks an initial step in creating enterprises based on local potential. In conclusion, this training not only improved the community's technical skills but also opened new opportunities for environmentally friendly and sustainable businesses.